Aquaculture waste nutrients removal using microalgae with floating permeable nutrient uptake system (FPNUS). (March 2022) - Li, Shouchun; Mubashar, Muhammad; Qin, Yufeng; Nie, Xifan; Zhang, Xuezhi
Graphical abstract: Highlights: FPNUS was tested for microalgae-based in-situ nutrient removal. N transfer rate across FPNUS varied with membrane pore size and type of N. NH4 + -N and NO3 – -N removal in aquaculture wastewater reached 1.32 and 1.89 mg L -1 d -1 . Modelled FPNUS to pond area ratio of 13% could balance typical N loading. Abstract: Large area requirements and huge energy consumption restrict the applications of microalgae in wastewater treatment. In this study, in-situ nutrient removal was tested using a floating permeable nutrients uptake system with pore sizes of 1, 5, 10, and 40 µm, and Chlorella sorokiniana and Scenedesmus acuminatus . Results showed that N transfer rate across FPNUS varied with membrane pore size and N-type. Average transfer rate of NH4 + -N, NO3 – -N, and NO2 – -N across 1 µm membrane was 2.6, 14.6, and 2.3 mg m -2 h −1, respectively, sufficient to support microalgal growth. The NH4 + -N and NO3 – -N removal rate in shrimp wastewater reached 1.32 and 1.88 mg L -1 d -1, comparable to some BNR processes used in RAS. According to the developed area ratio prediction model, FPNUS to pond area ratio of 21% is sufficient to balance N loading of 0.05 mg L -1 d -1 . These results indicate extraordinary potential of in-situ nutrient removal from wastewaters using FPNUS.